Simulation of Tribological Contacts in Hydraulic Machines - Roselin, Fredrik (Luleå tekniska universitet, Institutionen för teknikvetenskap och matematik, 2018)
Axial piston machines are operating at high pressure and varying speeds, which requires high reliability of the components. The machine components are separated by a fluid film, but sometimes this film gets penetrated by the surface asperities causing the machine to operate with metal-to-metal contact. In order to improve the design and predict the operating conditions might numerical tools be used. The goal with this thesis was to describe how the tribological contacts in Parkers machines can be modelled, considering oil and surface roughness. The so called Luleå Mixed Lubrication Model have therefore been investigated and it has been described how the model can be used in Parkers machines. The model uses a two-scale method to include the influence of real surface topographies of the components, it gives information about how the surface roughness affect the lubrication conditions. Different options of softwares have been investigated and compared to get an understanding of what possibilities and shortcomings they might have when it comes to this kind of simulations. Results show that all interesting contacts can't be treated the same, therefore must each contact be investigated separetly even though the Luleå Mixed Lubrication Model is used in all cases.